Multiscale geophysical imaging of the critical zone. (22nd January 2015) - Parsekian, A. D.; Singha, K.; Minsley, B. J.; Holbrook, W. S.; Slater, L.
Abstract Details of Earth's shallow subsurface—a key component of the critical zone (CZ)—are largely obscured because making direct observations with sufficient density to capture natural characteristic spatial variability in physical properties is difficult. Yet this inaccessible region of the CZ is fundamental to processes that support ecosystems, society, and the environment. Geophysical methods provide a means for remotely examining CZ form and function over length scales that span centimeters to kilometers. Here we present a review highlighting the application of geophysical methods to CZ science research questions. In particular, we consider the application of geophysical methods to map the geometry of structural features such as regolith thickness, lithological boundaries, permafrost extent, snow thickness, or shallow root zones. Combined with knowledge of structure, we discuss how geophysical observations are used to understand CZ processes. Fluxes between snow, surface water, and groundwater affect weathering, groundwater resources, and chemical and nutrient exports to rivers. The exchange of gas between soil and the atmosphere have been studied using geophysical methods in wetland areas. Indirect geophysical methods are a natural and necessary complement to direct observations obtained by drilling or field mapping. Direct measurements should be used to calibrate geophysical estimates, which can then be used to extrapolate interpretations over larger areas or to monitor changing processes over time. Advances in geophysical instrumentation and computational approaches for integrating different types of data have great potential to fill gaps in our understanding of the shallow subsurface portion of the CZ and should be integrated where possible in future CZ research.